Effects of limonene on ruminal fusobacterium necrophorum concentrations, fermentation, and lysine degradation in cattle - Saed Samii, Sina; Wallace, N.; Nagaraja, Tiruvoor G.; Engstrom, M. A.; Miesner, M. D.; Armendariz, C. K.; Titgemeyer, E. C. (My University, 2017)
Previous in vitro data showed that Fusobacterium necrophorum was inhibited by limonene. We further evaluated effects of limonene on growth of F. necrophorum in vitro as well as on ruminal concentrations of F. necrophorum in vivo. With in vitro cultivation in anaerobic brain-heart infusion broth, limonene decreased growth of F. necrophorum. Thymol also reduced growth of F. necrophorum, but it was less effective than limonene. Tylosin effectively reduced growth of F. necrophorum in vitro. Although the response over fermentation times and concentrations of antimicrobials differed somewhat between tylosin and limonene, the 2 antimicrobial agents yielded similar inhibitory effects on growth of F. necrophorum at concentrations ranging from 6 to 24 mg/L. The effects of limonene on ruminal F. necrophorum concentration in vivo were tested in 7 ruminally cannulated heifers (225 kg initial BW) used in a 7 × 4 Youden square design. Treatments included: 1) control, 2) limonene at 10 mg/kg diet DM, 3) limonene at 20 mg/kg diet DM, 4) limonene at 40 mg/kg diet DM, 5) limonene at 80 mg/kg diet DM, 6) CRINA-L (a blend of essential oil components) at 180 mg/kg diet DM, and 7) tylosin at 12 mg/kg diet DM. Each period included 11 d with 10 d washouts between periods. Samples of ruminal contents were collected before treatment initiation and after 4, 7, and 10 d of treatment for measuring F. necrophorum by the most probable number method using selective culture medium. Limonene linearly decreased (P = 0.03) ruminal F. necrophorum concentration, with the lowest concentration achieved with 40 mg of limonene/kg dietary DM. Limonene tended (P ? 0.07) to linearly reduce ruminal molar proportions of propionate and valerate while tending to linearly increase (P ? 0.10) those of butyrate and 2-methyl butyrate. Limonene did not affect ruminal NH3 concentrations or degradation rates of lysine. Neither CRINA-L (P = 0.52) nor tylosin (P = 0.19) affected ruminal F. necrophorum concentrations. CRINA-L significantly decreased ruminal concentrations of NH3 and molar proportions of 3-methyl butyrate, whereas tylosin significantly decreased molar proportions of propionate while increasing those of butyrate and tending to increase those of acetate. Limonene supplementation reduced ruminal concentrations of F. necrophorum suggesting that it may have the potential to reduce the prevalence of liver abscesses, although further research is needed to assess the effect of limonene in feedlot cattle. © 2016 American Society of Animal Science. All rights reserved.
Citation: Samii, S. S., Wallace, N., Nagaraja, T. G., Engstrom, M. A., Miesner, M. D., Armendariz, C. K., & Titgemeyer, E. C. (2016). Effects of limonene on ruminal fusobacterium necrophorum concentrations, fermentation, and lysine degradation in cattle. Journal of Animal Science, 94(8), 3420-3430. doi:10.2527/jas2016-0455
Keywords: Cattle; Essential Oil; Fusobacterium Necrophorum; Limonene; Rumen